Pengembangan Kreativitas Mahasiswa melalui Usaha Kerajinan Bunga Hias dari Kresek Bekas Bernilai Ekonomi - Muhammad Juwantho Lewa; Ilhamurahman Hubaib; Devi Eka Zulianti; Farel Pratama; Irwan Hifu; Lian Aminarti Wa Ode; Misbah; Tiara Savitri (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Plastic waste and the high unemployment rate among young people remain significant challenges that require innovative and sustainable solutions. This community service program aimed to develop the creativity of students and youth through the utilization of used plastic bags to create decorative flower crafts with economic value. The method employed was Project-Based Learning (PjBL), which actively involved participants in the stages of planning, implementation, and product evaluation. Data were collected through observation, documentation, and simple interviews. The program involved 7 participants who successfully produced 3 decorative flower arrangements made from used plastic bags as the final products of the training. The results showed that participants were able to transform plastic waste into products with aesthetic and economic value. In addition, participants acquired practical skills in plastic waste utilization and improved their understanding of waste management based on the principles of reduce, reuse, and recycle (3R). The activity also fostered environmental awareness and entrepreneurial spirit by encouraging participants to view plastic waste as a valuable resource for creative and marketable products. Therefore, the utilization of used plastic bags into decorative flower crafts can serve as an alternative community empowerment strategy that supports plastic waste reduction while promoting the development of the creative economy among young people.